2012
DOI: 10.1029/2011jd016772
|View full text |Cite
|
Sign up to set email alerts
|

Airborne and ground‐based observations of a weekend effect in ozone, precursors, and oxidation products in the California South Coast Air Basin

Abstract: [1] Airborne and ground-based measurements during the CalNex (California Research at the Nexus of Air Quality and Climate Change) field study in May/June 2010 show a weekend effect in ozone in the South Coast Air Basin (SoCAB) consistent with previous observations. The well-known and much-studied weekend ozone effect has been attributed to weekend reductions in nitrogen oxide (NO x = NO + NO 2 ) emissions, which affect ozone levels via two processes: (1) reduced ozone loss by titration and (2) enhanced photoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
153
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(180 citation statements)
references
References 75 publications
26
153
1
Order By: Relevance
“…Titration does not increase the sum of O 3 and NO 2 , whereas photochemistry with VOCs does. Therefore, variations in O x levels indicate that photochemistry with VOCs is important (Pollack et al, 2012). The average diurnal mixing ratios of O 3 and O x from NAPS measurements showing a maximum in the afternoon and being slightly higher on the weekends is also consistent with the average diurnal mixing ratios of HCHO showing a peak in the afternoon on weekends (Fig.…”
Section: O 3 No No 2 and Hchosupporting
confidence: 69%
“…Titration does not increase the sum of O 3 and NO 2 , whereas photochemistry with VOCs does. Therefore, variations in O x levels indicate that photochemistry with VOCs is important (Pollack et al, 2012). The average diurnal mixing ratios of O 3 and O x from NAPS measurements showing a maximum in the afternoon and being slightly higher on the weekends is also consistent with the average diurnal mixing ratios of HCHO showing a peak in the afternoon on weekends (Fig.…”
Section: O 3 No No 2 and Hchosupporting
confidence: 69%
“…Also, the OPE x,CAPS in this study is close to those reported in other cities, e.g., 2.5-4 for Nashville urban plume [Nunnermacker et al, 1998], 2.2-4.2 in New York City [Kleinman et al, 2000], and slightly lower than the range of 3.9-4.7 observed in Los Angeles, California [Pollack et al, 2012]. However, the OPE x in Beijing during summertime is observed to be higher by a factor of 2.4 compared to wintertime , indicating higher ozone production efficiency in summer than winter.…”
Section: Ozone Production Efficiency (Ope X )mentioning
confidence: 50%
“…Also, the low NO x concentration generally would lead to the high OPE x values (Figure 8). Another reason might be related to the wellknown phenomenon commonly referred to as the "weekend ozone effect" or "holiday effect" [Fujita et al, 2003;Pollack et al, 2012;Yarwood et al, 2003]. In these cases, Chou et al [2011] and Sun et al [2011] observed that enhancements in ozone are caused by reductions in NO x emissions on weekends that lead to enhancements in VOC/NO x ratio and ozone production efficiency.…”
Section: Ozone Production Efficiency (Ope X )mentioning
confidence: 99%
“…[49] It is well known that in California and the South Coast Air Basin, a large decrease in on-road diesel vehicle activity occurs on weekends, which leads to significant reductions in atmospheric species associated with diesel vehicles such as NO x , EC, specific VOCs, and particulate nitrate [Marr and Harley, 2002;Millstein et al, 2008;Pollack et al, 2012]. To explore if primary organic aerosols show an analogous weekend effect in Pasadena during CalNex, the diurnal cycles for HOA, EC, rBC, CIOA, CO, and benzene are plotted for weekdays and Sundays separately in Figure 10.…”
Section: Correlation Of Oxygenated Organic Aerosols With the Photochementioning
confidence: 99%